2008
DOI: 10.4314/ajcem.v9i3.7494
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of The Quality Of Locally Manufactured Antimicrobial Susceptibility Testing Discs Used In South Eastern Nigeria

Abstract: Locally manufactured antimicrobial susceptibility discs are becoming increasingly used in both private and government hospital laboratories in Nigeria. Data on the quality of these locally manufactured antimicrobial discs are not available. In order to provide some data, we evaluated the quality of three brands of locally manufactured antimicrobial susceptibility discs in common use in southeastern Nigeria. The three brands are Brodisk, Jirehdisk and Optudisc. The performances of these brands in agar disc diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 6 publications
3
9
0
Order By: Relevance
“…The use of different codes and in some cases, different concentrations for the same antibiotics (as in brands being used in this study) reflects a state of much confusion which makes it difficult to make a direct and comprehensive comparison of the performance of these two brands. Ekundayo and Omodamiro [21] also reported similar challenges in their related study. These discrepancies may be a reflection of lack of clear policy guidelines on antibiotic usage or failure of manufacturers to comply with such guidelines.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The use of different codes and in some cases, different concentrations for the same antibiotics (as in brands being used in this study) reflects a state of much confusion which makes it difficult to make a direct and comprehensive comparison of the performance of these two brands. Ekundayo and Omodamiro [21] also reported similar challenges in their related study. These discrepancies may be a reflection of lack of clear policy guidelines on antibiotic usage or failure of manufacturers to comply with such guidelines.…”
Section: Discussionsupporting
confidence: 63%
“…The excess of two discs may have accounted for un-interpretable zones of inhibition (i.e large zones of inhibition that merged together or completely wiped out bacterial growth at the time of reading the plates) which were encountered in the course of reading the antibiograms. Some authors who did a related study also reported this experience [21].…”
Section: Discussionmentioning
confidence: 55%
“…The following table summarizes results based on presence or absence of S. aureus and the age of the patient. Table 1 shows that the interval with both higher positive and negative results is [20][21][22][23][24][25][26][27][28][29] with 43.3 % and 32.5% respectively. The Table 1 also shows that 30 patients had S. aureus infection and 270 were free from it.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure of the AST was done as described by Ekundayo et al [21]. After incubation, the plates were examined and the zone of inhibition was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Clinically, antimicrobial susceptibility testing results provide guidance in the choice of antimicrobial agents in patient care [1]. The accuracy of results from antimicrobial susceptibility testing can be affected by multiple factors including the media, antimicrobial discs or preparations, inoculum's size, plate reading and incubation conditions [2].…”
Section: Introductionmentioning
confidence: 99%